Knowledge and attitude towards nursing profession among male secondary level students - Khatri, Asmita; Singh, Regina (Journal of Kathmandu Medical College, 2020)
Background: Nursing profession is stereotyped worldwide.  In Nepal, the enrollment of males in nursing education was initiated in 1986 AD with allocation of 10% seats, which stopped after enrollment of four batches only. Nepal Nursing council has announced 15% allocation of nursing seats to male students from academic year 2018/19 AD but only a few number of males have been enrolled. Objectives: The aim of this study was to determine the knowledge and attitude towards the nursing profession among male secondary level students. Methodology: A descriptive cross-sectional study was conducted by employing multi-stage sampling technique in June, 2019. Random list of secondary schools of Kathmandu district was created followed by proportionate stratified random sampling among 80% of male students studying in grades nine and ten from initial ten schools from the randomized list. The sample size was 388. A self-structured questionnaire was administered. Data was analyzed in SPSS version 20 by using frequency, percentage, mean, chi-square test and pearson’s correlation coefficient. Results: Out of 388 respondents, only 55.4% had adequate knowledge and only 53.4% had a more positive attitude towards the nursing profession. Significant association was found between knowledge towards the nursing profession with two of the socio-demographic variables grade of student and respondent’s family, friends and relatives in the nursing profession.Conclusion: The study showed inadequate knowledge and less positive attitude towards the nursing profession. Educational programs regarding different aspects of nursing profession should be planned timely by professional nursing organizations, nursing colleges and secondary schools of Nepal which would create a positive impact in enrollment of male nursing students in coming academic years.